2021
DOI: 10.3390/nano11092303
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Biomass-Based Carbon Nanoparticles into Polysulfone Ultrafiltration Membranes for Enhanced Separation and Anti-Fouling Performance

Abstract: Functionalized carbon nanomaterials are considered to be an efficient modifier for ultrafiltration membranes with enhanced performance. However, most of the reported carbon nanomaterials are derived from unsustainable fossil fuels, while an extra modification is often essential before incorporating the nanomaterials in membranes, thus inevitably increasing the cost and complexity. In this work, novel functionalized biomass-based carbon nanoparticles were prepared successfully from agricultural wastes of corn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The receiving material is a conductive aluminum foil covered with a PVDF nanofiber film and CC@PDA electrodes. After waiting for the end of electrostatic spinning, the nanofibers were dried in an oven at 60 °C for 5 h. Finally, an all-fiber-based friction nanogenerator (F-TENG) with built-in electrodes was obtained. CC@PDA should be accurately placed on the first layer of the PVDF nanofiber membrane and attached thereto based on bonding energy. Also, the CC@PDA should be kept at least 1 mm away from the edge of the nanofiber membrane, and the CC@PDA electrode layer should be properly wrapped between the two layers of the nanofiber membrane after the successful assembly of the F-TENG.…”
Section: Methodsmentioning
confidence: 99%
“…The receiving material is a conductive aluminum foil covered with a PVDF nanofiber film and CC@PDA electrodes. After waiting for the end of electrostatic spinning, the nanofibers were dried in an oven at 60 °C for 5 h. Finally, an all-fiber-based friction nanogenerator (F-TENG) with built-in electrodes was obtained. CC@PDA should be accurately placed on the first layer of the PVDF nanofiber membrane and attached thereto based on bonding energy. Also, the CC@PDA should be kept at least 1 mm away from the edge of the nanofiber membrane, and the CC@PDA electrode layer should be properly wrapped between the two layers of the nanofiber membrane after the successful assembly of the F-TENG.…”
Section: Methodsmentioning
confidence: 99%
“…Mahat et al [ 101 ] reported polysulfone functionalization with carbon quantum dots in order to improve the hydrophilicity of pristine PSF and antimicrobial properties. Zheng et al [ 103 ] proposed an increase of antifouling properties of polysulfone via carbon nanoparticles obtained from agricultural waste of corn stalks. The modified membranes improved hydrophilicity by increasing the pore size and modified roughness leading to improved membrane permeability and antifouling properties.…”
Section: Polysulfone Functionalized Membranes For Hemodialysismentioning
confidence: 99%